High Avidity dsDNA Autoantibodies in Brazilian Women with Systemic Lupus Erythematosus: Correlation with Active Disease and Renal Dysfunction - Rodrigo C. Oliveira; Isabela S. Oliveira; Mittermayer B. Santiago; Maria L. B. Sousa Atta; Ajax M. Atta (Journal of Immunology Research)
We investigated in Brazilian women with SLE the prevalence and levels of high avidity (HA) dsDNA antibodies and tested their correlation with lupus activity and biomarkers of renal disease. We also compared these correlations to those observed with total dsDNA antibodies and antibodies against nucleosome (ANuA). Autoantibodies were detected by ELISA, while C3 and C4 levels were determined by nephelometry. Urine protein/creatinine ratio was determined, and lupus activity was measured by SLEDAI-2K. The prevalence of total and HA dsDNA antibodies was similar to but lower than that verified for ANuA. The levels of the three types of antibodies were correlated, but the correlation was more significant between HA dsDNA antibodies and ANuA. High avidity dsDNA antibodies correlated positively with ESR and SLEDAI and inversely with C3 and C4. Similar correlations were observed for ANuA levels, whereas total dsDNA antibodies only correlated with SLEDAI and C3. The levels of HA dsDNA antibodies were higher in patients with proteinuria, but their levels of total dsDNA antibodies and ANuA were unaltered. High avidity dsDNA antibodies can be found in high prevalence in Brazilian women with SLE and are important biomarkers of active disease and kidney dysfunction.